Dynamics of Sulfentrazone Applied to Sugarcane Crop Residues - Carbonari, Caio A. [UNESP]; Gomes, Giovanna L. G. C. [UNESP]; Trindade, Maria L. B.; Silva, José R. M. [UNESP]; Velini, Edivaldo D. [UNESP] (Cambridge University Press (CUP), 2016)
The sulfentrazone is regularly applied to sugarcane crop harvest residue for PRE control of weedy species, especially in the dry season during the year, but little is known about how rainfall timing or crop residue mass affect the release of sulfentrazone into the soil and its subsequent effectiveness. Two experiments were conducted to examine the effects of sugarcane residue mass (5, 10, 15, and 20 t ha-1) and rainfall timing (1, 30, and 60 d after herbicide application) on sulfentrazone retention. Rainfall volumes were simulated at 2.5, 5, 10, 20, 35, 50, and 100 mm. A 20-mm rainfall volume was simulated at 7 and 14 d after the first simulated event. The water passing through the straw was collected after each rainfall simulation. The concentration of sulfentrazone was measured by liquid chromatography and mass spectrometry. The initial 20 mm of rain released the maximum mass of sulfentrazone from the sugarcane residue. The mass of sugarcane residue affected the amount of sulfentrazone recovered. The amount of sulfentrazone released from the residue was significantly reduced by the persistence on the residue surface for long periods before the occurrence of rain. During periods of low rainfall, recommendations for sulfentrazone rate must take into account losses that occur when applied over the harvest residues to design a weed-management plan that does not compromise efficacy and duration of the residual effects. Nomenclature: Sulfentrazone; sugarcane; Saccharum interspecific hybrids.
Keywords: herbicide; mulch; raw sugarcane; sorption